Kajian Literatur: Efektivitas Tanaman Kumis Kucing (Orthosiphon Stamineus) sebagai Alternatif Obat Anti-Diabetik - Intan Ardhita; Vriezka Mierza (Poltekkes Kemenkes Padang, 2025)
Diabetes mellitus (DM) is one of the degenerative diseases that requires long-term management to maintain stable blood glucose levels. The side effects of conventional antidiabetic drugs have prompted the search for alternative therapies that are safer and more effective. Orthosiphon stamineus (commonly known as Java tea or cat’s whiskers), a herbal plant well-known in Indonesia, contains active compounds such as flavonoids, tannins, and saponins that have potential antidiabetic properties. This article aims to review the potential of Orthosiphon stamineus in lowering blood glucose levels through a literature review of previous research findings. The method used is a literature review by searching databases such as Google Scholar and PubMed using keywords like